Localisation of vitamin D receptor in normal human duodenum and in patients with coeliac disease. Issue 9 (September 1994) - Colston, K W; Mackay, A G; Finlayson, C; Wu, J C; Maxwell, J D
Abstract : Immunocytochemistry using a specific monoclonal antibody 9A7 gamma was used to identify receptors for calcitriol (1, 25 (OH)2 D3), the active metabolite of vitamin D, in sections of duodenal mucosa. Specific staining for vitamin D receptors was largely restricted to nuclei of enterocytes lining crypts in duodenal biopsy specimens from normal mucosa. Vitamin D receptors were also abundant in crypts from duodenal mucosa in coeliac disease patients with mucosal damage and villous atrophy. In contrast, alkaline phosphatase, a vitamin D regulated protein, was absent from crypts but present on brush borders of normal villi, and on surface enterocytes in coeliac disease. Oestrogen receptor could not be identified in duodenal mucosa. These findings suggest that calcium malabsorption in coeliac disease does not result from the absence of vitamin D receptors, but rather from reduction in vitamin D regulated proteins and functions essential for active calcium absorption that are located in the enterocytes of the villi.